Cinobufagin-Loaded and Folic Acid-Modified Polydopamine Nanomedicine Combined With Photothermal Therapy for the Treatment of Lung Cancer - Li, Jianwen; Zhang, Zhanxia; Deng, Haibin; Zheng, Zhan (Frontiers in Chemistry, 2021)
Cinobufagin is used as a traditional Chinese medicine for cancer therapy. However, it has some disadvantages, such as poor water-solubility, short circulating half-life and low bioavailability. For improving the anticancer efficacy of cinobufagin, a targeted delivery and smart responsive polydopamine nanomedicine for cinobufagin delivery was rationally designed for the treatment of lung cancer in the present study. The modification of folic acid on the nanomedicine firstly mediated the tumor targeting by the interaction between folic acid and its receptor on tumor cells. After lysosomes escape, the PDA nanomedicine was triggered by the low pH level and released its cargo in tumor microenvironment. Combination with the photothermal therapy of polydopamine nanomaterial, the nanomedicine possesses better therapeutic effect for lung cancer. Compared with other nanomedicine with photothermal therapy, this nano-carrier was not only sensitive to biologically low pH level for on demand drug release, but also biodegradable into biocompatible terminal products. Therefore, the proposed drug delivery system with targeted delivery and smart release demonstrates the encouraging potential for multifunctional nano-platform applicable to enhance the bioavailability and reduce the side effects of chemotherapy agents.